Quranic Dhikr as Spiritual Healing: An Analysis of Fakhr al-Din al-Razi's Interpretation and Its Impact on Anxiety Phenomena Among Generation Alpha(الذكر القرآني كعلاج روحي: تحليل تفسير فخر الدين الرازي وآثاره على ظاهرة القلق لدى جيل ألفا) - Rochmad Rochmad; Dalia Zahrah; Ilham Habibullah; Ahmad Fadly Rahman Akbar; Mahmud Rifaannudin (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2026)
Purpose This study aimed to analyze the concept of Qur’anic dhikr in Fakhr al-Dīn al-Rāzi’s Tafsir Mafātīḥ al-Ghayb and to examine its relevance as a complementary approach to addressing the phenomenon of anxiety among Generation Alpha. Method This qualitative, literature-based study used thematic-critical analysis. Primary data from al-Rāzī's dhikr verse interpretations was evaluated using reduction, categorization, and interpretation stages. This study combined classical exegesis with modern psychology ideas including emotion management, cognitive reappraisal, and neurophysiological responses. Triangulation and a review of the current literature guaranteed data authenticity. Results/findings The study revealed Al-Rāzi believed that dhikr goes beyond linguistic engagement, as evidenced by research findings. According to research, al-Rāzī defines dhikr as a spiritual awareness process that impacts psychological stability, not just a linguistic exercise. Dhikr has cognitive, emotional, and neurophysiological elements. Generation Alpha anxiety is affected by digital exposure, social interaction, and cognitive development. Dhikr may complement modern psychology as a spiritual coping method. Conclusion Qur’anic dhikr can serve as an approach that integrates Islamic spirituality and modern psychology in addressing the anxiety of Generation Alpha. However, dhikr functions as a complementary therapy, not a substitute for clinical interventions. Further research is needed to determine its mental health benefits in the digital age.